The Innovative Business Behavior and Its Context: The Case of a Turbo Parts Company - Brenda Garcia Jarquin; Lilia Margarita Domínguez-Villalobos (Journal of Technology Management & Innovation)
The purpose of this document is to analyze the accumulation of technological capabilities and their interrelation with the spheres of context in a Mexican turbo parts company called Omega. The methodological design was that of a case study conducted with semi-structured interviews. The results show the accumulation of technological capabilities as driven by the catalyst of business and management capabilities, with R&D playing a relevant role at different levels of innovation. Regarding the spheres of context, the link with universities, research centers, CONAHCYT (National Commission for Humanities, Science and Technology), clients and suppliers has been a valuable resource for Omega. In the economic sphere, the perception of an unserved market and the drive to get ahead of the competition stand out. In the environmental sphere, the influence of client-requested environmental regulations, and in the political sphere, the effect of international industrial safety standards, have been a determining factor in several innovation decisions of the company. Finally, in the social and cultural spheres, the business environment of Querétaro stands out and the links with research centers, access to the PEI (Program of Economic Incentives) and the accumulated technological capabilities of the founder and the R&D director were the key elements for the birth and positioning of Omega as one of the main technology-based companies in Mexico and the world specialized in its field.